Poecilosclerida (Porifera, Demospongiae) collected by the Spanish Antarctic expedition BENTART-94 - Ríos, P.; Cristobo, F.J.; Urgorri, V. (Cahiers de Biologie Marine, 2004)
Two new species of Poecilosclerida Iophon hesperidesi sp. nov. (Iophonidae) and Isodictya bentarti sp. nov. (Isodictyidae) are described from material collected during the first Spanish expedition on the study of the Antarctic benthos, “Bentart ‘94”. A total of 67 individuals of Poecilosclerida (Demospongiae) were examined, corresponding to 14 species, 9 genera and 8 families. The individuals were collected from 13 stations in muddy sand, mud, stones, rocks, gravel and mixed sediment, at depths of 15 to 396 m. The specimens were collected by scuba diving, Van Veen dredge and rock dredge, on board the “Hespérides”.